Holger Friis, 75år - Glob, P. V. (Kuml, 1965)
HOLGER FRIIS 75 years Foremost among those who have worked with love and interest to unravel the prehistory of Jutland is Holger Friis. The dentist from Hjørring is known to all who have had the slightest contact with Danish archaeology. This is due not only to his long activity as museum worker and archaeologist, which nearly covers his 75 years -improbable as it may sound-but also as much to his fertile imagination and lively presentation of prehistory both on radio and television. He is the undisputed master on his home ground in Jutland's northernmost region. As an excavator, Holger Friis has more than half a century behind him. To the many unique discoveries he has made must be added thousands of more prosaic finds. What makes these so valuable is the skill with which they have been excavated and the many valuable observations made at the time. Moreover they are often interpreted with a freedom from prejudice which gives archaeology quite new perspectives. His work will always be fundamental to any study of the prehistory of Vendsyssel. Most of Holger Friis' finds are deposited in "Vendsyssels historiske Museum", the fine museum in Hjørring established the year before Holger Friis was born, mainly on the initiative of his father, Lønborg Friis, who was its first director. The museum also houses rich collections of rural culture up to the present day from North Jutland, material which would fetch thousands of pounds on the antique market, all collected by Holger Friis and his father, largely at their own expense. As a ten-year-old, Holger Friis was engaged at the museum as a custodian with a peaked cap at a wage of a penny a week - the largest wage he has ever received for his museum work, which has always meant money out of his own pocket. He has continued his father's valuable work and is now helped by his son, who himself has already fathered new small "museum curators". Danish archaeologists thank the Friis family for inspiration and hospitality. The close cooperation with the National Museum was initiated by Lønborg Friis and Sophus Müller, that strict, learned scholar and museum director who, in a letter, so cordially addressed Lønborg Friis as "My dear colleague and archaeological friend". The admiration which is apparent here was also given by Sophus Müller to Holger Friis, who is seen together with him in the photograph, during his last study visit in 1932 to the "Friises' Museum". We congratulate Holger Friis also with a: Dear colleague, archaeological friend! P. V. Glob.